2017
DOI: 10.18203/2394-6040.ijcmph20170767
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes among tuberculosis patients at an urban health centre, Goa, India- eight year retrospective record based study

Abstract: Background: India contributes the highest TB burden globally and DOTS being the key strategy of RNTCP needs evaluation. The objective of this study was to assess treatment outcomes in TB patients on DOTS in terms of success rates in new and retreatment cases. Methods: Retrospective record based study was conducted at urban health centre, Santa Cruz Goa, India including 135 TB cases registered from January 2008 to January 2016 for DOTS. Data on treatment outcomes was analysed using appropriate statistical metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
3
1
2
Order By: Relevance
“…12 TB is more common in male in our study which was similar to the study done by Veeramani G, Madhusudhan et al Since male are exposed more to external environment than female patients, there is increased burden on the male population. [13][14][15] The volume of TB cases diagnosed shows the burden on pulmonary cases and a large proportion of cases are sputum positive pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 89%
“…12 TB is more common in male in our study which was similar to the study done by Veeramani G, Madhusudhan et al Since male are exposed more to external environment than female patients, there is increased burden on the male population. [13][14][15] The volume of TB cases diagnosed shows the burden on pulmonary cases and a large proportion of cases are sputum positive pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 89%
“…We found that the overall TB treatment success (i.e. having an outcome of cured or treatment completed) at the end of the treatment was 86.2%, which is similar to other resource-constrained countries such as India (81-83%) [23][24][25], Ethiopia (85.6%) [26], Nigeria (83.1%) [27], Uzbekistan (83%) [28], Thailand (78.5-87.5%) [29], and higher than war affected countries such as Somalia (81.8%) [30], Iran (83.1%) [31] and Afghanistan (77.7%) [32]. However, the treatment success rate in our study was lower than the treatment success rate reported in the previous studies in Pakistan [13,33].…”
Section: Discussionsupporting
confidence: 69%
“…In this study, the overall TB treatment success rate is higher from previous published studies in different countries; studies from India reported the overall treatment success rates were (81%) [23], (83%) [24], (84.21%) [25], and (86%) [26], in Thailand the success rate was (78.5%) for patients in the TB Case Management cohort, while the success rate is high (87.5%) for patients in the National Health Security Office cohort [27], Iran (83.1%) [28], Uzbekistan (83%) [29], Denmark (80.5%) [30], Malaysia (67.26%) [31], Ethiopia (85.6%) [32], Somalia (81.8%) [33], Nigeria (83.1%) [34], in…”
Section: Discussioncontrasting
confidence: 59%